THE PROBLEM OF SELECTION OF INDICATORS, REFLECTING THE PROPORTION OF HIGH-TECH PRODUCTS IN THE GLOBAL MARKET - V. G. Zinov; N G. Kurakova; O. V. Cherchenko (Ekonomika Nauki)
The analysis of the portfolio of patent documents that do not have a Russian priority, issued to the citizens of the Russian Federation in foreign patent offices, was made. It is shown that, despite the provisions of the Civil and Administrative code of the Russian Federation and the Criminal code of the Russian Federation, the Russian inventors often obtain patents in foreign countries, bypassing the stage of filing of the application with the Russian patent office. Cross-country comparisons of the number of patent applications of residents of other States who have not received the priority of the respective country were made. It is shown that for US residents, for example, the share of such applications does not exceed 7%, while for residents of the Russian Federation accounts for almost 42%. The reasons that lead to an increase in the number of applications of Russian inventors that do not have priority of the Russian Federation and belong to foreign companies were studied. The main reason is the lack of interest from companies of the industrial sector of the Russian Federation for the advanced development.